Positive indicators of cattle welfare and their applicability to on-farm protocols - Giuseppe De Rosa; Fernando Grasso; Ute Knierim; Fabio Napolitano (Italian Journal of Animal Science, 2010)
Most of the research on animal welfare has focused on the negative aspects of the matter including an array of stress categories, whereas little has been done about the positive states of well being. The present study aims to describe indicators of positive animal welfare suitable for on-farm assessment. Appropriate environmental stimulation favours good welfare and, in an adequately enriched environment, positive indicators of welfare such as play behaviour tend to be more common. In addition, animals are motivated to perform these behaviours only if their primary needs are satisfied. In cattle, beneficial effects of social licking have been observed with positive correlation between being licked vs. milk production and weight gain, respectively. Ruminants are gregarious and a high degree of synchronisation within the herd may indicate a positive welfare state, in particular for subordinate animals. They may be able to meet their basic feeding and resting requirements performing these behaviours when the competition for a particular resource is low, however their welfare state would be improved if they could choose when and where (i.e. along with the other members of the group) to perform such behaviours. Due to the reduced applicability (mainly young animals), low feasibility (time consuming) and lack of research on reliability, play behaviour, albeit of proven validity, does not appear to be suitable for a rapid implementation in a welfare assessment scheme. Social licking is rarely expressed and its detection may be time consuming and scarcely feasible. Although validity and reliability need more studies, behaviour synchrony seems to be a promising positive welfare indicator as the instantaneous scan sampling technique makes this indicator easily applicable. Recently, a new methodology called “qualitative assessment of animal behaviour” has been developed. The method relies on a number of terms which are freely generated by observers. Thus, when positive aspects are observed they can be rated on a quantitative scale. Because of its high inter- and intra-observer reliability, this method appears to be the most promising.